2014
DOI: 10.1590/0104-6632.20140313s00002890
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between a conventional membrane bioreactor (C-MBR) and a biofilm membrane bioreactor (BF-MBR) for domestic wastewater treatment

Abstract: -In this paper, the influence of biofilm carriers in a MBR on the performance of organic matter and nitrogen removal and the influence on membrane fouling were evaluated. The configurations studied included a Conventional Membrane Bioreactor (C-MBR) and a Biofilm Membrane Bioreactor (BF-MBR) operated in parallel, both fed with domestic wastewater. Regarding organic matter removal, no statistically significant differences were observed between C-MBR and BF-MBR, producing an effluent with a Soluble COD concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
1
23
0
2
Order By: Relevance
“…This system significantly mitigates the biofouling, improves both the nitrification and denitrification processes of MBR. Similar results have been reported by Subtil, et al[54]. The authors reported no significant difference observed between the BF-MBR and MBR for COD removal.…”
supporting
confidence: 90%
“…This system significantly mitigates the biofouling, improves both the nitrification and denitrification processes of MBR. Similar results have been reported by Subtil, et al[54]. The authors reported no significant difference observed between the BF-MBR and MBR for COD removal.…”
supporting
confidence: 90%
“…This could be attributed to the fact that the rejection of monovalent ions such as Na + by NF is weak. 42,43 In addition, the pH did not affect the membrane rejection when the polyamide membrane pH operating range is 4-11. Figure 7 shows the results of RO for waste water treatment containing cations and anions using the old RO and new RO membranes.…”
Section: Resultsmentioning
confidence: 94%
“…42 While the membrane separation systems and the combination of these systems with other technologies, such as membrane bioreactors (MBR), are the most promising treatment technologies for effluent reuse. 43 Also, studies show that NF is an efficient treatment system for secondary or tertiary effluents aiming at the generation of water for industrial, agricultural, or indirect potable reuse. 44,45 …”
Section: Wastewatermentioning
confidence: 99%
“…As membranas possuíam porosidade média de 0,022 ± 0,006 µm, conforme descrito por Subtil et al (2012). O sistema de membranas de placa plana foi desenvolvido no CIRRA (Figura 4), sendo feito através da usinagem de placas de PVC, onde …”
Section: Módulo De Membranaunclassified